The rise of cybernetic citizenship - Wessel Reijers; Liav Orgad; Primavera de Filippi (Citizenship Studies, 2022)
The global COVID-19 pandemic demonstrates how states and companies mobilise new sociotechnical systems to track, trace, evaluate, and modulate the behaviour of citizens. This development illustrates an already-existing transformation of citizenship governance, which this article captures as the move to `cybernetic citizenship'. First, the article explores the concept of cybernetic citizenship, providing an overview of the concepts of `cybernetic' and `citizenship' and synthesising these in a discussion of the cybernetic modulation of citizenship. Second, it presents the rise of cybernetic citizenship in the urban realm, zooming in on the case of the Chinese social credit system and the way it affects civic life in the urban realm. Third, it turns into the normative implications of cybernetic citizenship, arguing that it confronts the idea of citizens as equal, free, and vigilant. It challenges equality by turning rights into ends, freedom by turning status into process, and civic virtue by turning excellence into effectiveness.
Keywords: 320; citizenship; cybernetic citizenship; COVID-19; social credit system; China